Reversible sulcal FLAIR hyperintensity on MRI in a migraine patient with aura - de Oliveira, Eduardo Portela (Radiol Case Rep, 2019)
Reversible sulcal fluid-attenuated inversion recovery (FLAIR) hyperintensity is a rare imaging finding that could be seen on magnetic resonance imaging (MRI), in patients with migraine with aura. Herein, we present a patient who was admitted to the emergency department with severe headaches, numbness on the right side of the body, and visual changes. MRI showed sulcal FLAIR hyperintensity in the occipital lobes, with no other abnormality. The patient was diagnosed with migraine with aura by neurology and the follow up MRI showed resolution of the finding, supporting the diagnosis. Sulcal hyperintensity on FLAIR is a nonspecific imaging finding that can occur with or without cerebral spinal fluid (CSF) abnormality. Although, clinical correlation and CSF analysis may be required, radiologists may often be able to suggest the cause of abnormal CSF signal depending on the distribution of sulcal FLAIR hyperintensity, and the presence of additional imaging findings.